Respostas
respondido por:
0
5 - [ 3+ ( 2 - 5)] =
\ /
5 - [ 3 + ( -3 )] =
5 - [ 3 -3 ] =
5 - [ 0 ] =
5 - 0 =
5
\ /
5 - [ 3 + ( -3 )] =
5 - [ 3 -3 ] =
5 - [ 0 ] =
5 - 0 =
5
respondido por:
0
É Só seguir uma sequência
Resolver primeiro parenteses , colchetes e o que sobrar
5-[3+(2-5)]
5 - [3+(-3)]
5 -[3-3]
5 - 0
5 → Resposta
Resolver primeiro parenteses , colchetes e o que sobrar
5-[3+(2-5)]
5 - [3+(-3)]
5 -[3-3]
5 - 0
5 → Resposta
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás